Inter-departmental correspondence
038-0029-001 Inter-Departmental THE LABOUR PARTY This form is for use when letters include subjects for attention by more than one Department From (Organisation) Name of Sender Address Date of Letter Subject (ONE SUBJECT ONLY) I have discussed this matter with Mrs. Miller, the Secretary of the National Joint Committee for Spanish Relief, who came to see me on the afternoon of Tuesday, December 9th, 1941. She gave the advice that if the Epsom Divisional Labour Party can no longer subscribe to the maintenance of the Basque children at Carshalton the matter should not be taken too seriously. Their contributions are not [essential] needed. The National Joint Committee have been getting money from the U.S.A. under the Foster Parents Scheme for the maintenance of these children. The Committee is now maintaining 400 Children; 330 are in homes - and in respect of them 10/- per head is paid to the foster parents - 70 are in hostels of whom 20 are at Carshalton. Through Miss Rathbone and Mr. Roberts the Committee are in touch with the Government which takes the view that as the Spanish Government is recognised by the British Government the refugee Basque children do not come within the Geneva Convention of Refugees and therefore the Government cannot make a grant to the Committee. If the position should change and we should find ourselves at war with Spain they themselves will make the necessary representations. There is no case for the Labour Party 'butting in now'. I think that a suitable reply should be sent to Mr. Bain who might be asked to state the difficulties of his Branch to Mrs. Miller. I think that in the circumstances as stated it is not necessary to seek the advice of the International Sub-Committee. Extracted by International Dept. To Mr. Middleton [Dept.] Date 11.12.41. L233156 292/946/38/29(I)